Gestión del departamento de Recursos Humanos de la Compañía Agrícola La Julia S.A. - Cuzco Espinoza, Bryam Luis (2020)
This case study was conducted with the purpose of detecting and analyzing the causes that affect the proper functioning of the Human Resources Department of the Agricultural Company La Julia S.A currently directed by the renowned Ecuadorian businessman Álvaro Noboa Pontón counts with an estimated 1,200 employees, dedicated to the export of tropical fruits mainly bananas. A qualitative research methodology was used through public documents with information relevant to the conduct of this case study, as well as interviews with the workers who made it possible to know exactly the level of conformity or non-conformity, opinions about the management carried out, to be able to determine which problems affect this department. Among the most relevant problems we could detect a limited retention of staff due to the lack of punctuality in payments, an inadequate working environment that leads to employees not remaining in a stable way in their job, inappropriate recruitment that causes inappropriate talent to be captured or that your skills, skills are not commensurate with what the position within the department requires, Training carried out in an irregular manner that have as consequences employees outdated in relation to knowledge, new skills that are of great importance to provide a quality service. The line of research applied in this case of study is Administrative Financial Management, tax, audit and control with the sub-Companies line and public and private institutions the career of commercial engineering as it is based on the relevant aspects in the organizational part of a private company.